Proyecto de evaluación del leasing financiero como una herramienta de financiación para pequeñas y medianas empresas (pymes) caso aplicado “acalosa s.a - Jines Muñoz, Angela M. (2009)
The purpose of this project is to analyze the financial leasing and its application on the PYMES mainly in the enterprise ACALOSA S.A; and by doing so, determinate if this way of financial would help the enterprise to have a foremost liquidity and thus increase its productive capacity. Particularly this research will be base on the application of the countable and tributary legislation effective in our country, the international normative, countable principles and other tools which would provide us with a deeper awareness of how the leasing operates in our financial system. To conclude the present study we will point the implicit benefits, legal, countable and tributary development and more; as much of the Financial Leasing as of the Bank Loans through the application applied to the enterprise ACALOSA S.A. gaining the knowledge of which one of these financial forms will give us a greater financial raise.